Virtual Bots Their Influence on Virtual Worlds, and How They Can Increase Interactivity and Immersion through VirtualPREX - Reiners, Torsten; Gregory, S.; Knox, V. (2016)
In 2011, seven academics from five Australian universities and one international university received an ALTC (Australian Learning and Teaching Council) grant to explore role play in a virtual world for professional experience, hence the project was called VirtualPREX. These academics are now all based at four institutions: the University of New England, Curtin University, Charles Sturt University, and RMIT University. Through VirtualPREX, pre-service teachers can practise their teaching in a risk-free environment before engaging in reallife professional experience. VirtualPREX provides a learning environment for pre-service teachers, where the use of role play in a virtual classroom is a key factor within distance education (Gregory et al., 2011). The pre-service teachers synchronously practise their teaching skills with peers through role-play activities in Second Life. We chose this virtual world for the project as all team members had existing, extensive experience in using Second Life as a teaching and learning tool. In the first phase of the project, we conducted a pilot study to test the virtual classroom environment where pre-service teachers were roleplaying as either a teacher or primary school student. The teacher presented a seven-minute teaching episode or provided an idea, and their peers acted as the primary school students in either an “on-task” or “off-task” role. This required synchronous role plays. Information for the on-task and off-task roles came from a focus group held with school teachers and principals. On-campus pre-service teachers conducted the role plays in a computer laboratory in which all participated. Off-campus pre-service teachers undertook the role-play activity from their own homes. The results of these synchronous role-play activities are discussed in the chapter, “VirtualPREX: Providing Virtual Professional Experience for Pre-Service Teachers” (see also Gregory et al., 2011). Another component of the project focuses on developing bots (non-player characters [NPCs], alternatively known as “animated pedagogical agents, conversational agents, chat bots, conversational avatars and virtual characters”: Veletsianos, Heller, Overmyer, & Proctor, 2010, p. 124) to act as the primary school students to provide asynchronous role play for pre-service teachers. Heller and Proctor (2010) emphasize that the term “agent” in virtual worlds does not have a consistent definition across disciplines, and even though these agents might use different technologies (for example, Artificial Intelligence Markup Language [AIML], as well as ALICE [Artificial Linguistic Internet Computer Entity]; FreudBot uses AIML), they are all virtual representations embedded in learning environments that serve pedagogical purposes. In VirtualPREX the use of agents or interactive bots will enable pre-service teachers to visit Second Life on their own time, in their own place, and at their own pace, to practise teaching the interactive bots before they embark on their real-life professional experience. This will be of particular benefit to off-campus pre-service teachers.